Implementation Of Investment Activities In The Field Tourist In The Samota Region Regency Sumbawa - Diman Ade Mulada; Nizai Kusuma Wardani; Titin Nurfatlah (Faculty of Law, University of Mataram, 2023)
This research aims to identify and examine the arrangements and supporting factors as well as obstacles to implementing investment activities in the tourism sector in the Samota region. This normative and empirical research uses statutory, conceptual, and practical approach methods. The results of the study show that the regulations governing investment activities in the tourism sector, especially in the Samota region, Sumbawa Regency, namely: Law Number 25 of 2007 concerning Investment , Law Number 10 of 2009 concerning Tourism , Presidential Regulation Number 97 of 2014 concerning Integrated Services One Door , Government Regulation Number 50 of 2011 concerning the 2010-2025 National Tourism Development Master Plan, Regulation of the Minister of Tourism and Creative Economy of the Republic of Indonesia Number 18 of 2016 concerning Registration of Tourism Businesses , Regulation of the Investment Coordinating Board (BKPM) Number 3 of 2021 concerning Electronically Integrated Risk-Based Business Licensing System , Investment Coordinating Board ( BKPM) Regulation Number 4 of 2021 concerning Guidelines and Procedures for Risk-Based Business Licensing Services and Investment Facilities , West Nusa Tenggara Provincial Regulation Number 7 of 2013 concerning Re Regional Tourism Development Master Plan 2013-2028 , Regional Regulation of West Nusa Tenggara Province Number 3 of 2015 concerning Investment, Regional Regulation of West Nusa Tenggara Province Number 2 of 2016 concerning Halal Tourism, Regional Regulation of Sumbawa Regency Number 7 of 2018 concerning Implementation of Tourism Business as well as supporting factors that influence investors interested in investing in tourism in the Samota region, namely: the Samota region has a lot of tourism potential, there is still a lot of vacant land, the availability of supporting transportation, the availability of infrastructure and security guarantees. While the inhibiting factors for tourism investment in the Samota area are: There are many overlapping land ownership, Difficulty obtaining clean water, and lack of promotion by the Regional Government.